2008
DOI: 10.1111/j.1540-8191.2008.00584.x
|View full text |Cite
|
Sign up to set email alerts
|

The Somatic Growth of Autologous Vessels in Venous Pathway After Extracardiac Total Cavopulmonary Connection

Abstract: The mid-term clinical results after the completion of the EC-TCPC, including the somatic growth of the venous pathway, were satisfactory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
(23 reference statements)
0
3
0
1
Order By: Relevance
“…Although some other patients also showed calcification in the conduit, no obstruction was seen in these patients. With regard to the geometrical changes in the Fontan pathway over time, we have previously demonstrated that the diameter of the pulmonary artery and length of the inferior vena cava above the hepatic vein insertion grow similarly to compensate for the lack of growth of the conduit [7]. Another major concern is the appropriate size of the conduit.…”
Section: Discussionmentioning
confidence: 99%
“…Although some other patients also showed calcification in the conduit, no obstruction was seen in these patients. With regard to the geometrical changes in the Fontan pathway over time, we have previously demonstrated that the diameter of the pulmonary artery and length of the inferior vena cava above the hepatic vein insertion grow similarly to compensate for the lack of growth of the conduit [7]. Another major concern is the appropriate size of the conduit.…”
Section: Discussionmentioning
confidence: 99%
“…El diámetro óptimo del mismo varía entre 16-18mm para niños de 2-3 años, mayores diámetros resultan en un mayor volumen estancado en la fase espiratoria. [22][23][24] Los principales reportes de este procedimiento en México proceden de los gru-…”
Section: Discussionunclassified
“…5,6 Unless there is considerable size mismatch between the extracardiac and central pulmonary artery conduits, unobstructed venous blood fl ow obtained by this method of reconstruction may outweigh the problem of a lack of growth potential of the prosthetic central pulmonary artery.…”
Section: Discussionmentioning
confidence: 99%